Asthma Drug Interactions in Patients Pediatric Inpatient Hospital X Jakarta - Mochamad Prasetyo Hardadi; Fatimah Fatimah (UHAMKA Press, 2020)
Asthma is a chronic disorder of the airways that is characterized periods of airflow obstruction. Asthma medication use in pediatrics is often encountered various problems. This study aims to determine the potential for drug interactions in pediatric asthma patients hospitalized in the Hospital X Jakarta period January 2015 to April 2017. This type of research is retrospective descriptive and analysis using the chi-square test. Retrieval of data through medical records with total sampling method. Based on the results of the study concluded that there are potential drug interactions of 31 patients (28.18%) and there are 48 cases of interaction. The most type of interaction mechanism is pharmacodynamic interaction in 33 cases (68.75%). The highest severity of interactions was moderate interactions in 40 cases (83.33%), and the highest onset of interactions was delayed onset of 32 cases (66.67%). The results of the chi-square analysis are shown from the probability value of 0.0000 (p-value <0.005), it can be concluded that there is a relationship between the amount of drug administration in a prescription with a significant drug interaction, and the results of the ods ratio indicate that the patient receiving the number of prescriptions in the drug ≥ 5 amounted to 0.244 times higher than the drug interactions that occur.